PERANGKAT PEMBELAJARAN BIOLOGI BERBASIS PROBLEM BASED LEARNING DAN BERORIENTASI KEMAMPUAN METAKOGNITIF - andi asyhari (Pendidikan Kimia Unimus, 2020)
Problem-based learning (PBL) in biology has been considered as one of the innovative contextual teaching designs, since students learn biology from problems (cases) of real life and it potentially encourage students’ metacognition. This research was aimed at developing biology teaching devices, grounded in problem-based learning approaches and metacognition habits, and identifying their effect on students’ learning achievement and metacognition. The large field testing was implemented on 33 students, using pre-experimental design group single pre-test – post test design. Experimental data was analysed quantitatively. The findings showed that (1) there was a significant effect of the use of the innovative lesson devices on student learning achievement and metacognition which is measured using questionnaire metacognitive (MAI). Metacognition scores were more likely to be improved, before and after treatment (0.36 middle). High metecognition scores were on planning aspects (0.42 middle) and the lowest score of metecognition was on executing aspects (0,29); (2) learning achievement was also improved, before and after treatment. N-gain score was 0.52 (middle). The total contribution of the lesson design on learning achievement and metacognition was classfied ‘highly effective’. Biology teachers could use the product to improve the quality of their teaching learning processes